(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the semantic similarities and differences between widely used idiomatic expressions in English and Uzbek. It examines the possibility of distortion of meaning as a result of literal translation of some units, and illustrates this process with examples. In addition, the role of expressions in the cultural context and the importance of expressing them through appropriate equivalences in the translation process are substantiated.